Comparative analysis of employment laws in protecting food riders: a path to fairness and balance - Mansor, Hariati; Mohd Salleh, Rezashah; Abu Bakar, Noraziah (2023)
The emergence of online platforms has led to the proliferation of the gig economy. It allows food riders the flexibility to choose when and where they work, and they are responsible for managing their own work arrangements. The freedom accorded to these riders is different from traditional full-time employment arrangements. Full-time employment status or an independent contractor is essential to determine the protection under the law. The paper poses the question of whether the amendment to the Employment Act 1955 in 2023 provides protection to food riders. To answer the question, the provisions of the Act will be analysed and as a basis of comparison the law in the UK and Australia will be referred. As such, the decision in Franco v Deliveroo Australia Pty Ltd (2021) and Uber BV and Others v Aslam and Others (2021) will be looked into. The paper’s finding indicates that even with the amendment to the Employment Act 1955, the court’s reliance on the traditional definitions of the employee remains crucial for obtaining legal protection. With the emergence of the gig economy, it is advisable to establish a clear provision that offers protection to these riders.